Proceedings of the 30th International Conference on Computer Graphics and Machine Vision (GraphiCon 2020). Part 2 2020
DOI: 10.51130/graphicon-2020-2-3-47
|View full text |Cite
|
Sign up to set email alerts
|

What is and What is not the Digital Earth

Abstract: The article addresses to a fundamental issue facing the concept of the Digital Earth in 2020 – what is the definition of the Digital Earth? 22 years after the announcement of the concept and 15 years after its first mass and successful implementation in the service Google Earth in 2005 this question remains unanswered. In the article the current status of the development of the Digital Earth concept by 2020 is considered, a methodology for the definition of the Digital Earth, based on the classification of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Geographic information systems (GIS) make it possible to bridge the gap between historical and traditional cartography and the cartography of the future, which is limited to a digital replica of planet Earth (Gao and Cao 2021;Novak and Ostash 2022). The evolution of cartographic representations can be traced from 1) maps and atlases that have a specific scale and projection to 2) globes, which allow one to view the hemisphere from different perspectives but not change the scale, and 3) GIS and geoportals, which allow one to choose the scale and the projection, to 4) a multi-resolution and three-dimensional digital Earth (Gore 1998), where we are not constrained by projection or scale (Eremchenko 2020), and 5) a historical digital Earth showing changes in the past to the as yet unknown 6) AI-driven digital Earth, digital Earth with near-live and live data presentation. Like the crystal ball from Bulgakov's novel The Master and Margarita, it has all the elements of a digital Earth: it shows live action in color, it shows the whole or part (zoom), it allows us to see the future (modeling), but it does not yet contain sound (Siepmann, Edler and Kühne 2021):…”
Section: Old Maps As a Challenge For The Futurementioning
confidence: 99%
“…Geographic information systems (GIS) make it possible to bridge the gap between historical and traditional cartography and the cartography of the future, which is limited to a digital replica of planet Earth (Gao and Cao 2021;Novak and Ostash 2022). The evolution of cartographic representations can be traced from 1) maps and atlases that have a specific scale and projection to 2) globes, which allow one to view the hemisphere from different perspectives but not change the scale, and 3) GIS and geoportals, which allow one to choose the scale and the projection, to 4) a multi-resolution and three-dimensional digital Earth (Gore 1998), where we are not constrained by projection or scale (Eremchenko 2020), and 5) a historical digital Earth showing changes in the past to the as yet unknown 6) AI-driven digital Earth, digital Earth with near-live and live data presentation. Like the crystal ball from Bulgakov's novel The Master and Margarita, it has all the elements of a digital Earth: it shows live action in color, it shows the whole or part (zoom), it allows us to see the future (modeling), but it does not yet contain sound (Siepmann, Edler and Kühne 2021):…”
Section: Old Maps As a Challenge For The Futurementioning
confidence: 99%
“…Задачу автоматического контроля изменений лесного покрова можно решить с помощью методов глубокого обучения с использованием данных дистанционного зондирования земли (ДЗЗ) [2]. На современном этапе развития спутниковых систем данные ДЗЗ находятся в открытом доступе и используются в широком спектре задач, связанных с поиском объектов определенного класса, детектированием изменений.…”
Section: разработка алгоритма определения изменений лесного покрова н...unclassified
“…In his speech of January 1998, US Vice President Al Gore first proposed the concept of "digital earth". Gore suggested that we need a "digital earth"-a virtual earth based on earth coordinates embedded with massive geographical data, with multiresolution and three-dimensional visualization [22][23][24]. A DC is an important part of "digital earth" and a concrete embodiment of "digital earth" in cities.…”
Section: Goals and Ideas Of DCmentioning
confidence: 99%